Adolescentes, redes sociais e educação - Peres Júnior, João Carlos (Universidade Federal de São Carlos, 2022)
This work aims to address the relationship between adolescence, social networks and education, considering the impacts that social networks can have on the lives of these developing individuals. focusing on changes in communication from the evolution of information and communication technologies; b) approach the teenager today and virtual social relationships, and c) explain the relationship between social networks and the educational area. For this, a narrative review was carried out on the subject, in which studies were identified in the scientific literature in areas of knowledge that address adolescence, especially the Human Sciences and Education. Initially, aspects that conceptualize what the internet and social networks are are focused, as well as the changes in social communication that occurred with the advent of these social networks. Next, adolescents in the 21st century are approached in the face of changes imposed by virtual social relationships, including aspects related to bullying and cyberbullying. Subsequently, it deals with the use of social networks and their relationship with the lives of adolescents and with Education. It is argued that social networks provided the creation of channels of communication, interaction and approximation between people, especially adolescents, but they can also influence processes of illness, exclusion and lack of commitment to life in society. In this sense, networks need to be used consciously and responsibly to ensure respect for people and social coexistence. In addition, it is considered that technologies are means that can be used in learning as long as the use is made within certain limits and pedagogical proposals configured according to the objectives of each educational institution.
Teenagers, social networks and education
Keywords: Redes sociais; Adolescência; Educação; Social networks; Adolescence; Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO